Uncaria tomentosa e Uncaria guianensis uma história agronômica a ser escrita - Honório, Isabela Cristina Gomes [UNESP]; Bertoni, Bianca Waléria (FapUNIFESP (SciELO), 2016)
The Uncaria tomentosa and Uncaria guianensis species, which are endemic plants in the Amazonian region, are highlighted as medicinal plants mainly because of their anti-inflammatory activity. The vegetal drug and various types of extracts have been commercialized by pharmaceutical industries and distributed in several countries, thus configuring the economic potential of both species. The objective of the present research was to collect agronomical data published in PubMed, SciELO, and Scopus databases and analyze the main subjects that were either investigated or not investigated to enable the production chain of these species. The conclusion is that U. guianensis has been less studied than U. tomentosa under all aspects evaluated. Both species have been exploited in an extractivistic way. However, no report was found on either sustainable management or conservation or domestication strategies or yet large scale production that can continuously attend the global demand of the pharmaceutic industry. Furthermore, the amount currently produced is insufficient to supply the program of the Ministry of Health, which intends to provide herbal drugs from Uncaria to all Brazilian cities.
Uncaria tomentosa and Uncaria guianensis an agronomic history to be written
Keywords: Cat’s claw; Extractivism; Medicinal plants; Uncaria